Sequence-dependent effects of hematoporphyrin derivatives (HPD) photodynamic therapy and cisplatin on lung adenocarcinoma cells - Li, Nana; Cui, Shichao; Yang, Aizhen; Xiao, Baohong; Cao, Yiwei; Yang, Xiaohui; Lin, Cunzhi (Photodiagnosis and photodynamic therapy, 2024)
•The order of the combination therapy (PDT + DDP / DDP + PDT) was important.•The cell viability in the PDT+DDP (HPD-PDT followed by DDP) group was significantly lower than that in the DDP+PDT (DDP followed by HPD-PDT) group.•A significant apoptotic profile and a high apoptotic rate were found in the PDT + DDP group.•The expression levels of BAX and cleaved-PARP increased, and those of Bcl-2 and Caspase-9 decreased in the PDT + DDP group.•The HPD-PDT followed by DDP significantly inhibited LUAD cell viability, which may be related to the mitochondrial apoptotic pathway. Hematoporphyrin derivatives (HPD)-Photodynamic therapy (PDT) in combination with cisplatin (DDP) is an effective anticancer strategy. However, whether the order of combination affects efficacy has not been studied. The human lung adenocarcinoma (LUAD) A549 cells were used as the study subjects. After A549 cells were treated with a single medication (PDT/DDP) or a sequential combination (PDT + DDP / DDP + PDT), the cell viability was assayed using the cell counting kit-8 method. Hoechst staining, Annexin-V/propidium iodide (PI) double staining, western blotting, and a real-time quantitative polymerase chain reaction (RT-qPCR) were performed to examine the mechanisms behind the combined effects. A synergistic impact between HPD-PDT and DDP was found. The cell viability in the PDT+DDP group was significantly lower than in the DDP+PDT group. A significant apoptotic profile and a high apoptotic rate were seen in the PDT + DDP group. The western blot showed that the expression levels of Bcl2-associated x(Bax) and cleaved-poly ADP-ribose polymerase (PARP) increased, and those of B-cell lymphoma-2 (Bcl-2) and Caspase-9 decreased in the PDT + DDP group. At the same time, the RT-qPCR revealed the upregulation of Bax and PARP mRNA and the downregulation of Bcl-2 and Caspase-9 mRNA. The order of the combination therapy (PDT + DDP / DDP + PDT) was important. The HPD-PDT followed by DDP significantly inhibited LUAD cell viability, which may be related to the mitochondrial apoptotic pathway.